Mathematical Problem Solving Skill Viewed from Epistemic Curiosity on Fostering Communities of Learners - Hasanah, Nur; Sri Noor Asih, Tri; Kharisudin, Iqbal (Universitas Negeri Semarang, 2021)
This research aims to describe mathematics problem solving skill viewed from epistemic curiosity of students on Fostering Communities of Learners of VIII graders about probability material. The design of this research was mixed concurrent – triangulation method. This mixed method took the research subjects purposively. They consisted of 6 students, each of 3 students with high and moderate epistemic curiosity. The findings showed that mathematics problem solving skill viewed from epistemic curiosity were varied. It was shown by 8 students with high epistemic curiosity whom obtained 4 high mathematics problem solving skilled students and 4 moderate skilled students. From 22 students with moderate epistemic curiosity, it obtained 10 high mathematics problem solving skilled students and 12 moderate skilled students. The students with high and moderate epistemic curiosity tended to be incapable in determining appropriate problem solving strategy.